STUDI DESKRIPTIF KASUS HIV PADA PEKERJA SEKS KOMERSIAL (PSK) DI LOKALISASI SLARANG TAHUN 2016 - Susbatiyarini Susbatiyarini; Siti Rofi'ah; Tuti Sukini; Masini Masini (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2017)
The incidence of HIV / AIDS infectious diseases tend to increase with a high mortality rate. The treatment of viral infection is currently only be able to slow the spread of the virus. The spread of the HIV virus is strongly influenced by the patterns of behavior and lifestyle. Commercial Sex Workers (CSW) is a high-risk group because it used to engage in sexual activity with a partner more than one partners, with a very high degree of mobility.The purpose of this study was to describe cases of HIV in CSW at Slarang Localization 2016.The research method is descriptive quantitative. This study population is CSW in Slarang Localization of Cilacap district some 69 people. The sampling technique use total sampling.The results showed that most of the young CSW with elementary education level. The knowledgement category of HIV is enough and mostly adhere to a medical examination. However, most PSK considers HIV disease is not dangerous even though the majority of CSW had preventive action the spread of HIV. All of CSW infected with HIV has been doing management in accordance with procedures but only 36.36% were dutifully taking ARVs.Suggested for health workers, especially for the field of infectious diseases in order to continue to conduct information on HIV and health checks periodically to CSW.